Psychiatric Morbidity among Caregivers of Schizophrenia Patients A Study in Tertiary Care Psychiatric Hospital in Dhaka (Journal of Current and Advance Medical Research, 2015)
Background: Severe mental illness like schizophrenia has far-reaching consequence for both patients and caregivers and their relatives and they also experience feeling of loss and grief. They are confronted with uncertainty and emotion of shame, guilt and anger like the patients they feel stigmatized and socially isolated. Caring for a family member with schizophrenia is an enduring stressor and causes considerable amount of burden. Objective: To assess mental health status of the caregivers of schizophrenia patients. Methodology: This descriptive cross sectional study was done among the caregivers of schizophrenia patients in outpatient and inpatient department of National Institute of Mental Health (NIMH), Dhaka, Bangladesh from September 2010 to February 2011. A semi-structured Questionnaire and General Health Questionnaire-28 (GHQ-28) were applied to the caregivers of schizophrenia patients who fulfilled the inclusion criteria. Among the respondents whose GHO-28 score were 4 or above Structured Clinical Interview for DSM-IV Axis I Non Patient (SCID-I/NP) version was applied to identify psychiatric disorders among the caregivers of schizophrenia.Results: Out of 272 respondents most of them were female (88.97%), housewife (72.42%) of 21 to 50 yrs age (80.51%). In this study 22.43% of respondents were suffering from different types of mental disorders. Among them major depressive disorder were most prevalent (11.8%). Other psychiatric disorders were found generalized anxiety disorder (4.8%), pain disorder (2.9%). Less common were panic disorder, social phobia, adjustment disorder and undifferentiated somatoform disorder (0.7% in each type).Conclusions: Significant proportions of the caregiver of schizophrenic patients were suffering from psychiatric disorders that did not get any psychiatric treatment.Journal of Current and Advance Medical Research 2015;2(1):12-17DOI:  http://dx.doi.org/10.3329/jcamr.v2i1.22581